Trends of increasing energy efficiency: opportunities of renewable and traditional energy sectors - D. A. Zhdanov; K. T. Moldabaev (Russian Journal of Economics and Law)
Objective: to study the trend of increasing energy efficiency in the modern economy, taking into account the possibilities of renewable energy generation, traditional (fossil) fuels and energy savings; to compare the parameters determining the speed of energy transformation.Methods: to achieve the set objective, a neoinstitutional methodological approach was used, and, in particular, methods of microeconomic analysis.Results: discussions about the advantages and prospects of renewable energy sources relative to traditional ones have been ongoing over the past decades. The performed analysis shows that traditional energy sources will continue to be the main ones for several decades to come. The paper analyzes the possibility of improving the energy efficiency of the economy, taking into account the prospects of renewable energy generation, traditional (fossil) fuels and energy savings, as well as the analysis of the impact of these factors on the speed of energy transformation.The selected tools allowed comparing the marginal costs of energy production and energy saving, and to determine their optimal volumes. Three directions of energy efficiency improvement are identified and analyzed: by activating energy saving as one of the available “alternative energy sources”; by reducing subsidies for traditional energy; and by differentiated taxation of various sources, taking into account environmental effects. Finally, it was shownhow the speed of energy transition is influencedby the impact of cost reduction for renewable energy sources, changes in fossil fuels tariffs, and inclusion of environmental externalities in its price.Scientific novelty: it is shown that the cost of energy saving is optimal for volumes when its marginal cost is equal to the marginal cost of solar energy; the ranking of factors that affect the speed of energy transformation is carried out: reducing the cost of renewable energy sources; various scenarios for the behavior of fossil fuel prices; and accounting for environmental costs.Practical significance: the results obtained can be useful for a model description of the interaction of the main factors that affect the increase in energy efficiency of the economy.